Eduardo Martin Quintana, El marxismo paradójico de Antonio Gramsci. Prólogo de Juan Luis Gallardo. Librería Huemul, Buenos Aires, 1990, 218 pp - Sacchi, Mario Enrique (1992)
Fil: Sacchi, Mario Enrique. Armada Argentina. Escuela de Guerra Naval; Argentina